Effect of the AM Fungus Sieverdingia tortuosa on Common Vetch Responses to an Anthracnose Pathogen - Ding, Tingting; Zhang, Weizhen; Li, Yingde; Duan, Tingyu (Frontiers in Microbiology, 2020)
Colletotrichum lentis Damm causes anthracnose of common vetch, or Vicia sativa L. It was first reported in China in 2019. This study evaluates the effects of the arbuscular mycorrhizal (AM) fungus Sieverdingia tortuosa (N.C. Schenck & G.S. Sm.) Błaszk., Niezgoda & B.T. Goto on growth and disease severity in common vetch. Our main finding is that the AM fungus did increase root biomass and reduce anthracnose severity of common vetch. Responses correlated with defense were also affected: chitinase activity, polyphenol oxidase (PPO) activity, the concentrations of jasmonic acid and proline, and the expression of resistance-related genes (e.g., upregulated "signal transduction," "MAPK signaling pathway," "chitinase activity," "response to stress," and the KEGG pathways "phenylpropanoid biosynthesis", "MAPK signaling pathways," and "plant-pathogen interactions"). These findings provide insight into the mechanism by which this AM fungus regulates the defense response of common vetch to C. lentis.